EMPOWERMENT STRATEGIES OF MICRO, SMALL, MEDIUM ENTERPRISES (MSMEs) TO IMPROVE INDONESIA EXPORT PERFORMANCE - Adi Adrian (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
In international trade itself can not be separated from the export and import sectors. One way that can be done to increase the value of exports is to improve the empowerment of products Micro, Small, Medium Enterprises. MSMEs is considered to be a solution in improving the economy in Indonesia. But the development of the era makes the challenges facing MSMEs is getting higher. The strategy that can be done by umkm in overcoming the development of the times is by the control of the market. However, in order to dominate the market, MSMEs need to get information easily and quickly to expand the marketing network of MSMEs. other than that Information technology application on SMEs will facilitate in expanding the market both in the country and overseas markets and the establishment of IT-based MSMEs Development Center.